2023
DOI: 10.1111/1744-7917.13248
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an odorant receptor responding to sex pheromones in Spodoptera frugiperda extends the novel type‐I PR lineage in moths

Abstract: In moths, pheromone receptors (PRs) are crucial for intraspecific sexual communication between males and females. Moth PRs are considered as an ideal model for studying the evolution of insect PRs, and a large number of PRs have been identified and functionally characterized in different moth species. Moth PRs were initially thought to fall into a single monophyletic clade in the odorant receptor (OR) family, but recent studies have shown that ORs in another lineage also bind type‐I sex pheromones, which indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Moth PRs are highly conserved and form a dedicated subfamily of ORs in the phylogenetic trees of moth ORs [69]. Recent studies have revealed novel lineages within OR clades responsible for detecting moth sex pheromones [26,[83][84][85][86][87], indicating multipe orgins of moths PRs. This perspective is resonable given the diverse structures of sex pheromones in moths.…”
Section: Discussionmentioning
confidence: 99%
“…Moth PRs are highly conserved and form a dedicated subfamily of ORs in the phylogenetic trees of moth ORs [69]. Recent studies have revealed novel lineages within OR clades responsible for detecting moth sex pheromones [26,[83][84][85][86][87], indicating multipe orgins of moths PRs. This perspective is resonable given the diverse structures of sex pheromones in moths.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of OR69, all of these are found, phylogenetically, scattered across various non-PR clades; it may be hypothesized that they would function in mediating female behaviors related to oviposition. On the other hand, OR69 clusters within the recently expanded novel PR clade [8,62]. Multiple ORs within this clade display sex-biased antennal expression in codling moth [27] and may play a role in mediating intra-species communication.…”
Section: Discussionmentioning
confidence: 99%
“…Three of these ORs presented as putative paralogues of previously identified ORs (OR11, OR12, and OR37), and were thus named respectively (OR11.2, OR12.2, and OR37.2). With the exception of OR69, all of the newly named ORs clustered with putative general odorant receptors; OR69 grouped within the newly expanded novel PR clade [62]. Of the 29 OR transcripts previously annotated, only 2 contained complete ORFs, and another 2 contained ORFs of at least 80% completeness.…”
Section: Odorant Receptorsmentioning
confidence: 99%